Winner of the Hédi Bouraoui Mediterranean Scholarship with Emphasis on the Maghreb, 2014 - Adjemian, Jonathan (Revue CMC Review, 2015)
Jonathan Adjemian, "On Mohammed Dib: Second contextualization - poetics: signs, and imagination." Jonathan Adjemian's essay is an excerpt from his doctoral dissertation in progress in Social and Political Thought, York University, "The World's Opacity: Writing and History in Mohammed Dib." It was the 2014 winner of the Hédi Bouraoui Scholarship in Mediterranean Studies with Emphasis on the Maghreb.